Gallbladder Wall Thickness to Predict Severe Dengue in Children - Prashanth, S N; Jagwani, Harshita; Das, Sudha Kiran; Kumar, Jagadish; Murthy, Srinivasa (Journal of Nepal Paediatric Society, 2021)
Introduction: Significant increase in plasma leakage is characteristic of severe dengue. This results in collection of fluid in serous cavities. Gall bladder wall thickening (GBWT) often precedes the development of pleural effusion and ascites. Early detection of plasma leakage and management is shown to reduce mortality in dengue illness. Ultrasonography is a point of care investigation to identify GBWT. The aim of this study was to determine the cut-off value of GBWT to predict severe dengue in the early phase of the illness. Methods: This was a prospective study done on 310 children with dengue illness. Abdomen and chest ultrasound was done in all these children between third and sixth day of illness. GBWT of more than 3.5 mm was taken as a thickened gall bladder wall. Maximum severity of the illness was considered for categorising the severity of dengue. Results: Out of 310 children, 160 (51.6%) were categorized as dengue fever, 91 (29.4%) as dengue with warning signs and 59 (19%) as severe dengue. The incidence of thickened gall bladder wall was 27.5% in DF (Dengue fever), 68% in DF with warning signs and 96.6% in severe dengue. The odds of finding thickened gall bladder wall in severe dengue are 3.5 times that of dengue fever. GBWT increases as the severity of the illness increases. GBWT of 5 mm has sensitivity of 93.7% and specificity of 70% to predict progress to severe dengue. There was a fair correlation of 46% between thickened gall bladder wall and thrombocytopenia. Gall bladder wall thickness of 2.5 mm had sensitivity of 86.3% and specificity of 80% for ascites. GBWT of 3.5 mm had a sensitivity of 77.6% and specificity of 85% for pleural effusion. Conclusions: GBWT assessment by ultrasonography in early phase of illness can be used as a point of care modality to predict severe dengue. The sensitivity and specificity to predict the progression to severe dengue is 93.7% & 70% respectively for the cut-off value of five mm of GBWT.